What is a painting (The Metropolitan Museum seminars in art, 1986)
Analyzes the paintings of Whistler's Mother and the Mona Lisa to show the misconceptions in art appreciation concerning intellectual and emotional response. Describes how a particular object looked, and tells how the people of that time felt about it.